2020
DOI: 10.3390/insects11080522
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation and Male Glossina austeni Mating Performance

Abstract: An area-wide integrated pest management (AW-IPM) strategy with a sterile insect technique (SIT) component has been proposed for the management of African animal trypanosomosis (AAT) in South Africa. In preparation for the SIT, the mating performance of colony reared Glossina austeni males under influencing factors such as radiation dose and the development stage that is exposed to radiation, was assessed under laboratory and semi-field conditions. The radiation sensitivity of G. austeni colonized 37 years ago … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 77 publications
5
15
0
1
Order By: Relevance
“…As a result, these findings suggest that the irradiation dose currently used to sterilized tsetse flies could be optimized according to the dose rate. This parameter was not taken into account in past studies [ 17 , 31 , 41 , 42 , 43 ] and the fine tuning of the dose and dose rate and could lead to more competitive sterile males.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these findings suggest that the irradiation dose currently used to sterilized tsetse flies could be optimized according to the dose rate. This parameter was not taken into account in past studies [ 17 , 31 , 41 , 42 , 43 ] and the fine tuning of the dose and dose rate and could lead to more competitive sterile males.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of 40 to 80 Gy induced 97–99% sterility in G. brevipalpis females when mated with males irradiated as late-stage pupae or adults [ 181 ]. Higher doses, 80 to 100 Gy, were required for G. austeni males irradiated as late-stage pupae or adults to induce similar levels of sterility in females [ 182 ]. The mating performance of colony flies irradiated as adults and late-stage pupae, as investigated in walk-in field cages, indicate the irradiated males to be as competitive to mate with females as un-irradiated males [ 181 , 182 ].…”
Section: Main Research Achievements—livestock Pestsmentioning
confidence: 99%
“…Mating performance of irradiated male insects is one of the key factors that need to be evaluated before the implementation of SIT releases. De Beer and colleagues (2020) [ 24 ] report that irradiation of Glossina austeni males from a 37 year-old colony as adults or late stage pupae to obtain ca. 99% sterility did not affect their mating performance, and it was concluded that these sterile males are suitable for SIT applications as shown in laboratory and semi-field experiments.…”
Section: Livestock Pestsmentioning
confidence: 99%